Multivariate statistical analysis of parameters of surface water quality in Vojvodina - Borko Matijević; Đenđi Vaštag; Tomin Milena Bečelić; Suzana Apostolov; Božo Dalmacija (Zaštita Materijala)
Monitoring of chemical and physical-chemical parameters of surface water is a very important factor in the quality control and management. Surface water quality is largely determined by atmospherics (natural process) and the discharge of industrial and municipal waste water (anthropogenic process). By applying different statistical methods (multivariate statistical analysis) can significantly reduce the bulkiness of the available data obtained by monitoring, and therefore the correct interpretation of the results of the quality and the ecological status of water. In this paper, using multivariate statistical analysis (cluster analysis, factor analysis and principal components analysis) processed the results of the analysis of surface water in AP Vojvodina during the 2011 year. Based on the results of statistical analysis it could by identified the main factors that have an impact on the ecological status and ecological potential of water flows. In this way it can improve the existing monitoring network.